Contribution of intermediate-volatility organic compounds from on-road transport to secondary organic aerosol levels in Europe - S. E. I. Manavi; S. E. I. Manavi; S. N. Pandis; S. N. Pandis (Atmospheric Chemistry and Physics, 2024)
Atmospheric organic compounds with an effective saturation concentration (C∗) at 298 K between 103 and 106 µg m−3 are called intermediate-volatility organic compounds (IVOCs), and they have been identified as important secondary organic aerosol (SOA) precursors. In this work, we simulate IVOCs emitted from on-road diesel and gasoline vehicles over Europe with a chemical transport model (CTM), utilizing a new approach in which IVOCs are treated as lumped species that preserve their chemical characteristics. This approach allows us to assess both the overall contribution of IVOCs to SOA formation and the role of specific compounds. For the simulated early-summer period, the highest concentrations of SOA formed from the oxidation of on-road IVOCs (SOA-iv) are predicted for major European cities, like Paris, Athens, and Madrid. In these urban environments, on-road SOA-iv can account for up to a quarter of the predicted total SOA. Over Europe, unspeciated cyclic alkanes in the IVOC range are estimated to account for up to 72 % of the total on-road SOA-iv mass, with compounds with 15 to 20 carbons being the most prominent precursors. The sensitivity of the predicted SOA-iv concentrations to the selected parameters of the new lumping scheme is also investigated. Active multigenerational aging of the secondary aerosol products has the most significant effect as it increases the predicted SOA-iv concentrations by 67 %.